2001
DOI: 10.1111/j.1151-2916.2001.tb00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Chemistry and Stabilization in Air of Brannerite, UTi2O6

Abstract: Brannerite, UTi 2 O 6 , can be formed only under low oxygen pressures by dry ceramic processing techniques, but the substitution of ϳ0.2 and 0.3 formula units (fu) of Ca or Gd, respectively, for U allows the stabilization of the phase in air. The Ca/Gd in brannerite provides charge compensation for some U to exist in valence states >؉4, as found by X-ray absorption spectroscopy of the U L III -edge. The maximum solubilities of Ca and trivalent rare earths in the air-fired samples, 0.3 and 0.5 fu, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 5 publications
7
53
3
Order By: Relevance
“…of U (Ca 0.2 Y 1.7 U 0.1 Ti 2 O 7 and Ca 0.6 Y 1.1 U 0.3 Ti 2 O 7 ) was targeted as U 5+ showed broad, probably phonon-assisted bands in the vicinity of 5000-6000 cm À1 and 7000-12,000 cm À1 , with these wavenumber ranges as expected for U 5+ [23,26]. In addition there were sharp zero-phonon lines at $6700 cm À1 (see Fig.…”
Section: Y 2 Ti 2 O 7 -Based Samplesmentioning
confidence: 94%
See 1 more Smart Citation
“…of U (Ca 0.2 Y 1.7 U 0.1 Ti 2 O 7 and Ca 0.6 Y 1.1 U 0.3 Ti 2 O 7 ) was targeted as U 5+ showed broad, probably phonon-assisted bands in the vicinity of 5000-6000 cm À1 and 7000-12,000 cm À1 , with these wavenumber ranges as expected for U 5+ [23,26]. In addition there were sharp zero-phonon lines at $6700 cm À1 (see Fig.…”
Section: Y 2 Ti 2 O 7 -Based Samplesmentioning
confidence: 94%
“…When Pu-doped LaPO 4 monazite ceramics are fired in air at 1000-1200°C, the substitution of divalent Ca or Pb in the trivalent La site allows the valence of Pu to change from trivalent to tetravalent [22]. For U in brannerite (UTi 2 O 6 ) in which U is normally tetravalent, the substitution of divalent or trivalent ions in the U site leads to the formation of U 5+ in both air and neutral (Ar) atmospheres [23][24][25]. Similar behaviour is found for U in zirconolite (CaZrTi 2 O 7 ) [26], and zircon [27].…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse reflectance spectroscopy revealed the presence of U 5+ ions, which suggested that stabilization of these doped phases was via a charge compensation mechanism rather than the formation of oxygen vacancies (7). No evidence of green fluorescence characteristic of U 6+ was observed.…”
Section: Solid Solution Rangementioning
confidence: 98%
“…Natural specimens of UTi 2 O 6 exhibit chemical flexibility, with significant substitution of Pb, Ca, Th, Ln, on the U site, and Si, Al, Fe on the Ti site, commonly observed (Ln¼lanthanide) [7][8][9][10][11][12][13][14][15]. Closely related synthetic solid solutions, incorporating pentavalent uranium, have also been described by several authors [16][17][18][19]. Natural brannerites are generally found to be X-ray amorphous due to accumulated damage from the recoil daughters of U and Th a-decay [14].…”
Section: Introductionmentioning
confidence: 94%